Designing and assessing experiential learning pedagogy for an intercultural communicative competence training module: a quasi-experimental study - Wibowo, Agus Hari; Mohamad, Bahtiar; Djatmika,; Santosa, Riyadi (Frontiers in Education, 2024)
Intercultural communicative competence (ICC) is crucial for future workers in the global job market, where many feels unprepared to communicate effectively with culturally diverse colleagues. Therefore, university students must develop this skill to stay competitive. Experiential learning pedagogy, focused on ICC training, can enhance final-year students’ abilities, offering an alternative to traditional teaching methods. To examine the effectiveness of experiential learning pedagogy in a redesigned ICC module for undergraduates, a multiple-group pre-test and post-test quasi-experimental design was adopted. Data were collected from 31 undergraduate students at two public universities in Indonesia. The module was redesigned to incorporate experiential learning pedagogy, providing various opportunities through face-to-face training workshops. Validated and reliable instruments measured students’ experiential level with the pedagogy and their competencies in intercultural communication. Descriptive and inferential statistics were used to analyze the data. Participants showed a substantial enhancement in the Intercultural Communicative Competency Scale after the training workshop, as evidenced by higher post-test scores compared to pre-test scores. Additionally, the post-test data demonstrated a moderate improvement in participants’ expectations from the pre-test for the experiential learning pedagogy. The findings prove the effectiveness of both the content and the pedagogy of the module. Furthermore, these modules should continually integrate more interactive elements to better meet learners’ needs.